Listener Proficiency and Shared Background Effects on the Accentedness, Comprehensibility and Intelligibility of Four Varieties of English. (5th November 2019) - Hansen Edwards, Jette G.; Zampini, Mary L.; Cunningham, Caitlin
Abstract : This study examines the impact of Hong Kong listeners' English language proficiency on the intelligibility and perceived accentedness and comprehensibility of speakers of English from Hong Kong, China, Singapore and the United States. The study had two main aims: (1) to examine how proficiency impacts listeners' perceptions of how accented and comprehensible different varieties of English are and how this differs from speech intelligibility; (2) to examine whether listeners benefited from a shared background effect differently by proficiency level. The research findings have pedagogical implications as they can improve understanding of which proficiency levels may benefit most from instruction and how a shared background may mitigate proficiency effects. They also help researchers understand the extent to which listeners' own English proficiency impacts their evaluations of the speech characteristics of other speakers of English, an area of research that is still relatively unexplored.